Quantitative serum proteomic analysis among tobacco habitudes and oral potentially malignant disorders: A Case-control study - Hemant Bhutani; Vasavi K Santosh; Sandeep Pagare; Anindya Kr Debnath; Mandavi Waghmare; Naveen Kumar Shetty (Wolters Kluwer Medknow Publications, 2023)
Background: Oral cancer is the sixth most common cancer, with India having the largest burden. Oral potentially malignant disorders (OPMDs) refer to oral mucosal disorders with increased risk for malignancy. Tumour markers aid in cancer diagnosis and tumor burden evaluation, while serum proteomics uses quantitative protein level measurements that characterizes biological processes. Objectives: To evaluate variance in levels of total serum proteins, albumin, globulin, A/G ratio across healthy individuals, tobacco and areca nut users and in patients with oral potentially malignant disorders (OPMDs) and whether it can be used as a diagnostic marker in those that develop OPMDs. To assess whether there is a variance in the protein markers in different OPMDs like leukoplakia, oral submucous fibrosis and tobacco pouch keratosis. Methodology: 70 individuals were considered in the study out of which 10 patients were healthy individuals, 30 were oral habitudes and 30 were oral habitudes and OPMDs. Results: Among the individuals, total serum proteins and globulin showed variance among habitudes and OPMDS, albumin and A/G did not show any statistically significant results. Conclusion: Study provides evidence that serum proteomic analysis of total serum proteins and globulin can be used as a diagnostic marker to facilitate detection of OPMDs.